PERANAN SEKTOR INDUSTRI TEKSTIL DAN PRODUK TEKSTIL (TPT)TERHADAP PEREKONOMIANINDONESIA: ANALISIS INPUT-OUTPUT - Taris Fajri; Hermin Triyowati (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
This study aims to determine how well the number of direct and indirect linkages, index of power deployment and index of the degree of sensitivity as well as the multiplier output, income, and labor sectors of textiles and textile products within the scope of the Indonesian economy in 2005. To get the purpose of the study analysis, this research is done by analyzing the data on Indonesian Input-Output Table 175 sectors in 2005. Analyzed data from the Input-Output Table is a data transaction on the basis of domestic producer prices. These sectors are aggregated into 68 sectors. This is done to see the impact of deployment and linkage textiles and textile products to other sectors of the economy. In the analysis of data, fiber and yarn spinning industry has backward linkages value is smaller than the linkages in the future. Textile industry (fabric), the apparel industry (garment), and the other has a value of industrial textiles backward linkages greater than the relationship in the future. In the analysis of the spread of the power index, industrial fiber and yarn spinning, textile (cloth), industry apparel (garment), and the textile industry was able to increase the upstream sector growth or increase the output of other sectors that are used as inputs by industry sector itself because it has the power dispersion index value greater than one. Power dispersion index greater than one means that the sector is able to enhance the growth of the upstream sector. Analysis of the degree of sensitivity index, industrial textile (cloth), the apparel industry and textile industry can’t afford to encourage the production of the downstream sector which uses the input from the industrial sector as it has a degree of sensitivity index values ​​less than one. In the multiplier analysis, for the analysis of output multipliers, the apparel industry has the largest output multiplier of the other sub-sectors is equal to 2.4647. For household income multiplier, fiber and spinning sector has multiplier largest household income from other sub-sectors is equal to 0.1644. In the employment multiplier, fiber and spinning sector had the largest employment multiplier of other sub-sectors is equal to 0.0214. From the analysis of the data, it can be concluded that the textile and clothing sector is the sector that Indonesia was in a position downstream of where the sector is a sector that produces an output that is directly consumed by final consumers. If the Government can properly optimize the sector, then the sector of textiles and textile products may act as a puller outputs of upstream sectors